2018
DOI: 10.3390/app8122442
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Linkage between Economic Growth, Electricity Access, Energy Use, and Population Growth in Pakistan

Abstract: Electricity is a versatile form of energy that plays a vital role in fulfilling the daily requirements of human life. The primary aim of this study was to investigate and explore the link between economic growth, electricity access, energy use, and population growth in Pakistan for the period 1990–2016. An autoregressive distributed lag (ARDL) bounds testing approach to cointegration was applied to investigate the causality link between the study variables. These tests shed light on the long-run connection amo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…FDI comes from four major sectors: energy, banking and finance, telecommunications, and food and beverages [50]. Pakistan's economy had been growing at an average rate of over 7.6% per annum from 2003 to 2008 [50], which increased the demand for energy [52], as exhibited in Figure 2. Agriculture is the backbone of Pakistan's economy and has been designated by the government as the engine of national economic growth and poverty reduction; the mix trends in this sector are due to the availability of water and technological resources, and the economic growth in 2007 was highly linked to agriculture production [50].…”
Section: Data Collectionmentioning
confidence: 99%
“…FDI comes from four major sectors: energy, banking and finance, telecommunications, and food and beverages [50]. Pakistan's economy had been growing at an average rate of over 7.6% per annum from 2003 to 2008 [50], which increased the demand for energy [52], as exhibited in Figure 2. Agriculture is the backbone of Pakistan's economy and has been designated by the government as the engine of national economic growth and poverty reduction; the mix trends in this sector are due to the availability of water and technological resources, and the economic growth in 2007 was highly linked to agriculture production [50].…”
Section: Data Collectionmentioning
confidence: 99%
“…Certainly, with depletion of natural gas reserves, Pakistan has to rely on liquefied natural gas (LNG) import, and so from 0.7% to 8.7% overall share of LNG in energy end-use from 2015 to 2018 [52]. Moreover, economic growth and population growth link with an increase in overall energy end-use of a country, and for Pakistan, from 2013 to 2018 GDP growth was around 30% and annual population growth stated greater than 2% [53]. Pakistan Energy Efficiency and Conservation Board (PEECB) is the governing body that looks after energy efficiency related policies and programs.…”
Section: Energy Management System Programs For Industrial Sector In Pmentioning
confidence: 99%
“…Moreover, the industrial service sectors in the GDP may increase energy intensity. Rehman and Deyuan ( 2018 ) analyzed the role of GDP in energy consumption in Pakistan using an autoregressive distributed lag (ARDL). The results demonstrated that energy usage and urban population growth have a significant impact on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is believed that energy is the lifeblood of the economy, which is subject to policies and market forces of demand-supply. It is equally important for both developed and developing economies and for industrial sectors to achieve economic development and social stability (Rehman and Deyuan 2018 ). The consistencies of energy-related policies are dependent on economic, political, and environmental factors that decide the technology to achieve future demand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation